The Effect of Eight Weeks of High Intensity Interval Training (HIIT) on the Content of Mitochondrial Fission and Fusion Proteins in the Left Ventricle of Old Rats - Mahdi Marezloo; Neda Aghaei Bahmanbeglou; Hamed Alizadeh pahlavani; Habib Asgharpour (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: As individual grow older, the likelihood of developing cardiovascular diseases increases significantly. Currently, high-intensity interval training (HIIT) is regarded as a strategy for exercise to improve heart disease. Consequently, the aim of this research was to investigate the impact of eight weeks of HIIT on the levels of PINK1 and PARKIN proteins in the left ventricle of aged rats. Methods: The present research was of an experimental type and involved twelve male rats, each 20 months old, with an average weight of 400 ± 30 grams. The rats were randomly divided into HIIT and control groups (each group had 6 rats). The HIIT program consisted of high-intensity bouts of 85-95% of maximum speed (m/min) and active rest periods with an intensity of 40-55% of maximum speed (m/min) during each weekly session. Following a 48-hour period post the most recent training session, the rats were subjected to anaesthesia through the administration of Ketamine and Xylazine.  Subsequently, the left ventricle of the heart was excised, and the various parameters were measured utilizing the western blot laboratory technique. Data were analysed using the Shapiro-Wilk test and independent t-test conducted within SPSS16. A significance threshold of P≥0.05 was considered for this analysis. Results: Eight weeks of HIIT caused a significant increase in PINK1 (P=0.02) and PARKIN (P=0.004) protein levels in the left ventricle of aged rats, in comparison to the control group. Conclusion: It seems that HIIT may influence the quality of mitochondria within the left ventricle of the hearts of aged rats, indicating potential implications for health-related applications.